2009
DOI: 10.1111/j.1540-8175.2009.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Thickness Is Increased in Nonhypertensive Turner's Syndrome

Abstract: HR, LV wall thicknesses, LVMI and the LADi are significantly increased in normohypertensive TS women. There is also subclinical diastolic dysfunction in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
5
12
0
Order By: Relevance
“…Previous study showed that LVMI was >95 g/m 2 in 32.2% of TS patients and in 3.3% of the control group . In accordance with previous study, LVMI of TS patients (66.3 ± 9.94) were significantly higher than those of controls (54.14 ± 6.92).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous study showed that LVMI was >95 g/m 2 in 32.2% of TS patients and in 3.3% of the control group . In accordance with previous study, LVMI of TS patients (66.3 ± 9.94) were significantly higher than those of controls (54.14 ± 6.92).…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies concerning LV diastolic function in TS reported similar results in Doppler echocardiographic studies attributed to LV diastolic dysfunction . Another study showed that E/A ratio was <1 in 6.45% of TS patients and in 3.3% of control group . The presence of diastolic dysfunction in a group of children with no predisposing conditions is remarkable and may represent a syndromic trait in Turner's patients.…”
Section: Discussionsupporting
confidence: 54%
“…The addition of a left ventricular mass estimate to conventional risk assessment improves prognostication in the general population 7 . This may also be the case for TS, where an abnormal left ventricular phenotype of unresolved etiology is a cardinal trait 8–10 . The left ventricle characteristically appears hypertrophied with subclinical diastolic and systolic dysfunction, and left atrial enlargement may be present 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…7 This may also be the case for TS, where an abnormal left ventricular phenotype of unresolved etiology is a cardinal trait. [8][9][10] The left ventricle characteristically appears hypertrophied with subclinical diastolic and systolic dysfunction, and left atrial enlargement may be present. [8][9][10] Current etiological understanding of left ventricular abnormalities in TS is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation